Study and Review of Properties and Applications of Portland Pozzolana Cement - Jagruti Dattatraya Waghmare; Samruddhi Sampatrao Patil; Sheha Mahadeo Patil; M. Maske (ASEAN Journal of Science and Engineering, 2021)
Portland Pozzolana Cement (PPC) is prepared by adding Pozzolanic materials to ordinary Portland Cement. The artificial pozzolana materials used in the manufacturing of PPC such as fly ash, silica fume, rice husk, blast furnace slag, are actually industrial waste, which is produced in large amounts. These artificial pozzolana materials when used in concrete can reduce consumption of natural resources, diminish the effect of pollutants in the environment and it is economical and reliable. The main objective of this paper is to focus on the properties and applications of Portland Pozzolana Cement and make effective use of different industrial by-products in the manufacturing of cement. We found that both PPC and ordinary portland cement (OPC) are commonly used types of cement in construction. Nowadays, PPC is used as a substitute for ordinary Portland cement (OPC cement). Since PPC contains pozzolanic materials, it helps to enhance the strength of concrete. The quantity of PPC required in making the concrete is less when compared to OPC. PPC is a green material that contributes towards sustainable development.